Pigment epithelium-derived factor regulation by human chorionic gonadotropin in granulosa cells. Issue 2 (February 2016) - Bar-Joseph, Hadas; Ben-Ami, Ido; Ron-El, Raphael; Shalgi, Ruth; Chuderland, Dana
Abstract : Human chorionic gonadotropin (hCG) is a known trigger of ovarian hyperstimulation syndrome (OHSS), a potentially life-threatening complication of assisted reproduction. Administration of hCG results in the release of vascular endothelial growth factor (VEGF) from the ovary. We have previously shown that expression of pigment epithelium-derived factor (PEDF) in granulosa cell line is regulated by hCG, reciprocally to VEGF, and that the PEDF–VEGF balance is impaired in OHSS. Our aim was to explore the signaling network by which hCG downregulates the expression of PEDF mRNA and protein in granulosa cells. We applied specific chemical inhibitors and stimuli to human primary granulosa cells and rat granulosa cell line. We found that PKA and protein kinase C, as well as EGFR, ERK1/2 and PI3K, participate in the signaling network. The finding that hCG-induced PEDF downregulation and VEGF upregulation are mediated by similar signaling cascades emphasizes the delicate regulation of ovarian angiogenesis.